Candidiasis profile at the outpatient department of the university of cape coast hospital in the central region of Ghana: a retrospective study - Kwame Kumi Asare; Hilda Amuaku Bentil; Emmanuel Gyesi; Samuel Amoah; Felicity Bentsi-Enchill; Yeboah Kwaku Opoku (BMC, 2023)
Abstract Introduction Vulvovaginal candidiasis (VVC) is a public health problem with an estimated 138 million women globally experiencing recurrent VVC annually. The microscopic diagnosis of VVC has low sensitivity, but it remains an essential tool for diagnosis as the microbiological culture methods are limited to advanced clinical microbiology laboratories in developing countries. The study retrospectively analyzed the presence of red blood cells (RBCs), epithelial cells (ECs), pus cells (PCs) and Candida albicans positive in wet mount preparation of urine or high vaginal swabs (HVS) samples to test for their sensitivity and specificity for the diagnosis of candidiasis. Methods The study is a retrospective analysis at the Outpatient Department of the University of Cape Coast between 2013 and 2020. All urine and high vagina swabs (HVS) cultures samples using Sabourauds dextrose agar with wet mount data were analyzed. 2 × 2 contingency diagnostic test was used to ascertain the diagnostic accuracy of red blood cells (RBCs), epithelial cells (ECs), pus cells (PCs), and Candida albicans positive in wet mount preparation of urine or high vaginal swabs (HVS) samples for the diagnosis of candidiasis. The association of candidiasis among patients' demographics was analyzed using relative risk (RR) analysis. Results The high prevalence of candida infection was among female subjects 97.1% (831/856) compared to males 2.9% (25/856). The microscopic profiles which characterized candida infection were pus cells 96.4% (825/856), epithelial cells 98.7% (845/856), red blood cells (RBCs) 7.6% (65/856) and Candida albicans positive 63.2% (541/856). There was a lower risk of Candida infections among male patients compared to female patients RR (95% CI) = 0.061 (0.041-0.088). The sensitivity (95%) for detecting Candida albicans positive and red blood cells (0.62 (0.59-0.65)), Candida albicans positive and pus cells (0.75 (0.72-0.78)) and Candida albicans positive and epithelial cells (0.95 (0.92-0.96)) with corresponding specificity (95% CI) of 0.63 (0.60-0.67), 0.69 (0.66-0.72) and 0.74 (0.71-0.76) were detected among the high vaginal swab samples. Conclusion In conclusion, the study has shown that the presence of PCs, ECs, RBCs or ratio of RBCs/ECs and RBCs/PCs in the wet mount preparation from urine or HVS can enhance microscopic diagnosis of VVC cases.